Safety and mid-term outcome of catheter ablation of ventricular tachycardia in octogenarians. Issue 8 (10th November 2016) - Frontera, Antonio; Panniker, Sandeep; Breitenstein, Alexander; Bruno, Vito Domenico; Connolly, Georgia May; Wilson, David; Rio, Teresa; Dhinoja, Mehul B.; Hussain, Wajid; Schilling, Richard J.; Thomas, Glyn; Wong, Tom; et al.
Abstract: Aims: Radiofrequency (RF) catheter ablation (CA) is superior to standard medical therapy in controlling recurrent ventricular tachycardia (VT). The majority of procedures have been performed in a middle-aged population. The outcome of VT ablation in the elderly has not been described. Methods and results: We retrospectively studied the outcome and safety of CA of VT in octogenarians performed in four European centres. The population consisted of patients presenting with recurrent VT refractory to medical therapy. Patients aged over 80 years were compared with younger patients undergoing CA. Clinical characteristics, procedural data, complications, and outcomes were examined. Implantable cardioverter-defibrillator (ICD) therapy data were collected. A total of 54 consecutive octogenarian patients underwent RF CA of VT and represented the study group (42 males, age 82.8 ± 2.7 years) compared with a control group of 104 younger patients (85 males, age 66.7 ± 8.9 years). Mean follow-up was 33 ± 48 months. Implantable cardioverter-defibrillators were present in 81 and 86% of patients, respectively ( P = 0.93). Left ventricular ejection fraction was 29% ± 8.2 in octogenarians vs. 34% ± 10.2 in the younger group ( P < 0.01). More major complications occurred in octogenarians (18 vs. 2%, P < 0.01). During follow-up, there were more ICD shocks in the octogenarians (28 vs. 15%, P < 0.01). The Kaplan–Meier curve of survival after VT ablation confirms comparable survival rates at 1 year, but the elderly have poor survival in the mid-term. Survival in the elderly post VT ablation is comparable with that in an age-matched cohort with ICDs but no VT storm. Conclusion: Octogenarians undergoing CA of VT have more risk factors, higher risk of complications and ICD shocks, but demonstrate comparable short-term survival rates.